Triple-decker sandwich complexes with a bent cyclo-P5 middle-deck. Issue 83 (28th September 2016) - Mädl, Eric; Peresypkina, Eugenia; Timoshkin, Alexey Y.; Scheer, Manfred
Abstract : New types of triple-decker complexes with an organo-substituted P5 middle-deck were synthesized by the reaction of [Cp*Fe(η 4 -P5 R)] − (1a : R = CH2 SiMe3 ;1b : R = NMe2 ) with halogeno-bridged transition metal dimers [Cp′′′MX]2 (M = Cr, Fe, Co, Ni; X = Cl, Br). Abstract : New types of triple-decker complexes with an organo-substituted P5 middle-deck were synthesized by the reaction of [Cp*Fe(η 4 -P5 R)] − (1a : R = CH2 SiMe3 ;1b : R = NMe2 ) with halogeno-bridged transition metal dimers [Cp′′′MX]2 (M = Cr, Fe, Co, Ni; X = Cl, Br). By oxidation of [(Cp*Fe)(Cp′′′Co)(μ, η 4:3 -P5 CH2 SiMe3 )]2a with [Cp2 Fe][PF6 ], the cationic complex [(Cp*Fe)(Cp′′′Co)(μ, η 5:4 -P5 CH2 SiMe3 )] + was isolated. The electronic structure of the synthesized complexes was elucidated by DFT calculations.